2019
DOI: 10.1103/physreve.100.052137
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic uncertainty relations including measurement and feedback

Abstract: Thermodynamic uncertainty relations quantify how the signal-to-noise ratio of a given observable is constrained by dissipation. Fluctuation relations generalize the second law of thermodynamics to stochastic processes. We show that any fluctuation relation directly implies a thermodynamic uncertainty relation, considerably increasing their range of applicability. In particular, we extend thermodynamic uncertainty relations to scenarios which include measurement and feedback. Since feedback generally breaks tim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 72 publications
0
55
0
Order By: Relevance
“…1 for biomolecular processes in the linear response regime. A generalized version of the TUR had been proposed and tested for various systems under driving [8][9][10][11][12]16 . Nevertheless, generalized TURs (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1 for biomolecular processes in the linear response regime. A generalized version of the TUR had been proposed and tested for various systems under driving [8][9][10][11][12]16 . Nevertheless, generalized TURs (see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, we find the TUR to be valid in a temperature- and voltage-biased QPC. We note that recently, it has been shown that a weaker, generalized TUR applies whenever a fluctuation theorem holds [ 46 , 47 ]. Here, we show further constraints on the TUR under the restriction that the thermoelectric element produces power, necessary to define a useful performance quantifier.…”
Section: Introductionmentioning
confidence: 99%
“…We aim to partially answer this question in a simple setup (described below) driven out of equilibrium using an arbitrary time-dependent external protocol. A generalization of [50] for the broken time-reversal symmetry using the time-reversed current observable is given in [51,52].…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty relations for both of these observables are obtained using the second law of thermodynamics as well as the positive semi-definite property of the correlation matrix of work and degrees of freedom of the system in both underdamped and overdamped regimes. There are four main features of the paper: (1) the thermodynamic uncertainty relations are obtained from the second law of thermodynamics, (2) the external protocol need not be time-symmetric, (3) in contrary to [51,52], there is no need to compute the observable in the time-reversed protocol, (4) the cost function is given by work done on the system in the overdamped regime.…”
Section: Introductionmentioning
confidence: 99%